2007
DOI: 10.1042/bj20070149
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TNF-α with a tetravalent mini-antibody TNF-TeAb

Abstract: Anti-TNF-alpha [anti-(tumour necrosis factor-alpha)] therapy is widely considered to be among the most efficient treatments available for rheumatoid arthritis, psoriatic arthritis and inflammatory bowel disease. In the present study a tetravalent mini-antibody, named 'TNF-TeAb', was constructed by fusing the tetramerization domain of human p53 to the C-terminus of an anti-TNF-scFv [anti-(TNF-alpha-single-chain variable fragment)] via a long and flexible linking peptide derived from human serum albumin. TNF-TeA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…In silico docking experiments with CFTR F508del suggest that the VX-809 aromatic ring(s) occupies a hydrophobic pocket at the NBD1/CL4 (cytoplasmic loop) interface [41,42], as well as interact at the NBD1/NBD2 interface and NBD1-CL1/MSD1 interface [42]. Thus, it is likely that correctors that bind to distinct sites on CFTR and additively address multiple structural issues will be required to achieve substantial clinical efficacy, and even with NBD1 corrected and the interfaces restored, potentiators may be needed to achieve full functionality [4,34,4345]. …”
Section: Structural Mechanismsmentioning
confidence: 99%
“…In silico docking experiments with CFTR F508del suggest that the VX-809 aromatic ring(s) occupies a hydrophobic pocket at the NBD1/CL4 (cytoplasmic loop) interface [41,42], as well as interact at the NBD1/NBD2 interface and NBD1-CL1/MSD1 interface [42]. Thus, it is likely that correctors that bind to distinct sites on CFTR and additively address multiple structural issues will be required to achieve substantial clinical efficacy, and even with NBD1 corrected and the interfaces restored, potentiators may be needed to achieve full functionality [4,34,4345]. …”
Section: Structural Mechanismsmentioning
confidence: 99%
“…Currently, it is generally accepted that pro-inflammatory cytokines play an important role in the pathogenesis of RA [6][7][8][9]. Therefore, several treatment methods for RA aim to block certain cytokines such as tumor necrosis factor (TNF) and interleukin-1 (IL-1), noted to be essential in the development of RA [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…1. The tetravalent antibody was a homotetramer formed association of four scFv fusion products with residues 319-360 of the human p53 [15]. Results of size exclusion HPLC indicated that the purified protein exhibited a major peak (65.5%) with a retention time appropriate for the tetramer and a minor (34.5%) peak with a retention time appropriate for the dimer (Fig.…”
Section: The Production Of the Tetravalent Anti-dr5 Antibodymentioning
confidence: 93%
“…The scFv, HSA (human serum albumin) -p53 gene, comprising residues 490-513 of HSA [14] and residues 319-360 of the human p53 [15,16] was assembled by an overlapping PCR with seven synthetic oligonucleotides ( Table 1). The PCR product was cloned into the eukaryotic expression vector pSecTag2A.…”
Section: The Production Of the Tetravalent Anti-dr5 Antibodymentioning
confidence: 99%